The Black reproductive : unfree labor and insurgent motherhood - Kaplan, Sara Clarke (University of Minnesota Press, 2021)
"How Black women's reproduction became integral to white supremacy, capitalism, and heteropatriarchy-and remains key to their dismantling"--